PERSIAPAN SEKOLAH RAMAH ANAK DI SALATIGA: PEMETAAN KEBUTUHAN DAN IDENTIFIKASI MASALAH DARI PERSPEKTIF PESERTA DIDIK - Susilowati, Linda (KRITIS, 2018)
Obtaining a quality education is the foundation to creating sustainable development. Education can help locals to develop innovative solutions for the world’s problems. Schools then have a very important role to play in achieving quality education. In addition to improving quality in the academic field, developing quality school human resources is also very important task to do. Schools need to support the human recources or children’s development by creating child-friendly schools. In the preparation phase of creating the child-friendly schools, there are several im parts that need to be considered and carried out, such as open discussion or constultation with the children as student in order to identify children’s needs and accommodate children’s aspiration. The focus group discussion and interviews with representative students from Salatiga founds there are needs and problems that need to be addresses on preparing the child-friendly schools: 1) on school policy: schools need partipations of all stake holders in developing school policy of violence against student, and specific detail of that upcoming policy, clearer and safer violence reporting mechansism for children; 2) on learning activities: unbalance treatments and discrimination towards students (based on social status, religion, and race or ethnicity), lack of educators’ capacity on understanding the diversity of character and students’ potential, treatments from educator that decreasing students’ condidence, teachers behavior that contains offensive SARA (ethnicity, religion, race, and social class), and violence cases both physically and verbally in schools activities; 3) on educators component; lack of understanding of child rights and child-friendly schools, lack of implementation of child rights and child-friendly schools; 4) on facilities and infrastructure: evacuation routes for natural disasters and fires, clean toilet facilities and changing rooms that can protect students from sexual crimes attempts; 5) on students participations and; 6) stakeholders participations: lack of stakeholders and students involment on preparing child-friendly school in Salatiga.